Cambios y permanencias en la atmósfera cultural trans femenina de Ciudad de México - Gutiérrez Martínez, Ana Paulina (El Colegio de México, 2019)
In this paper I analize some changes and permanences of cultural elements and social practices of the trans femenine cultural atmosphere of México City. This text gives some light about these processes by three life stories reconstructed with documental, biographical and ethnographic methods. These narratives allow us to notice transformations and permanence in two important fields: the shapes of collective organization and the type of resources for communication and expression of gender identities. It is possible to distinguish two phases with differential uses of these cultural resources that trans femenine persons use to configure and express their gender identity in some urban sociabilities in Mexico City.